Combinatorial Pattern Matching 22nd Annual Symposium, CPM 2011, Palermo, Italy, June 27-29, 2011. Proceedings - Giancarlo, Raffaele; Manzini, Giovanni (Springer eBooks., 2011)
This book constitutes the refereed proceedings of the 22nd Annual Symposium on Combinatorial Pattern Matching, CPM 2011, held in Palermi, Italy, in June 2011. The 36 revised full papers presented together with 3 invited talks were carefully reviewed and selected from 70 submissions. The papers address issues of searching and matching strings and more complicated patterns such as trees, regular expressions, graphs, point sets, and arrays. The goal is to derive non-trivial combinatorial properties of such structures and to exploit these properties in order to either achieve superior performance for the corresponding computational problems or pinpoint conditions under which searches cannot be performed efficiently. The meeting also deals with problems in computational biology, data compression and data mining, coding, information retrieval, natural language processing and pattern recognition.